2023
DOI: 10.1039/d3ee02129g
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the reorganization energy and crystal packing of small-molecule donors enables the high performance of binary all-small-molecule organic solar cells with a slow film growth rate

Tongle Xu,
Jie Lv,
Daming Zheng
et al.

Abstract: Difficulty in tuning the ideal phase morphology of interpenetrating network structures is the main reason for the relative inefficiency of all-small-molecule organic solar cells (ASM-OSCs). Achieving a desirable phase morphology...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Uncontrollable nucleation and crystal growth kinetics is one of the important reasons for poor quality of PVK films. It has been widely reported that specific organic salts and additives are very effective in modulating the nucleation and crystal growth rate of PVK films. In addition, when preparing large-area PVK films, the researchers used phosphonic acid or sulfonic acid molecular additives to regulate the crystal growth rate of PVK and the uniformity of the film. In the two-step process of a small-area PVK film, the addition of MDPPO to lead iodide changed the morphology of lead iodide, and the organic cation fully reacted with lead iodide (Figure S3). In the large-area PVK film with a one-step method, interaction between MDPPO and PVK promoted the crystallization of PVK (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Uncontrollable nucleation and crystal growth kinetics is one of the important reasons for poor quality of PVK films. It has been widely reported that specific organic salts and additives are very effective in modulating the nucleation and crystal growth rate of PVK films. In addition, when preparing large-area PVK films, the researchers used phosphonic acid or sulfonic acid molecular additives to regulate the crystal growth rate of PVK and the uniformity of the film. In the two-step process of a small-area PVK film, the addition of MDPPO to lead iodide changed the morphology of lead iodide, and the organic cation fully reacted with lead iodide (Figure S3). In the large-area PVK film with a one-step method, interaction between MDPPO and PVK promoted the crystallization of PVK (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%